Construction, Expression, and Characterization of a Recombinant Immunotoxin Targeting EpCAM - Minghua Lv; Feng Qiu; Tingting Li; Yuanjie Sun; Chunmei Zhang; Ping Zhu; Xiaokun Qi; Jun Wan; Kun Yang; Kui Zhang (Mediators of Inflammation)
Epithelial cell adhesion molecule (EpCAM) is a type I transmembrane glycoprotein overexpressed in human epithelioma but with relatively low expression in normal epithelial tissues. To exploit this differential expression pattern for targeted cancer therapy, an EpCAM-targeted immunotoxin was developed and its antitumor activity was investigated in vitro. An immunotoxin (scFv2A9-PE or APE) was constructed by genetically fusing a truncated form (PE38KDEL) of Pseudomonas aeruginosa exotoxin with an anti-EpCAM single-chain variable fragment (scFv). ELISA and flow cytometry were performed to verify immunotoxin (scFv2A9-PE or APE) antigen-binding activity with EpCAM. Cytotoxicity was measured by MTT assay. Confocal microscopy was used to observe its cellular localization. The results of ELISA and flow cytometry revealed that the immunotoxin efficiently recognized recombinant and natural EpCAM. Its antigen-binding activity was relatively lower than 2A9. MTT assay confirmed potent reduction in EpCAM-positive HHCC (human hepatocellular carcinoma) cell viability (IC50 50 pM). Immunofluorescence revealed that the immunotoxin localized to endoplasmic reticulum 24 h later. In conclusion, we described the development of an EpCAM-targeted immunotoxin with potent activity against tumor cells, which may lay the foundation for future development of therapeutic antibody for the treatment of EpCAM-positive tumors.